Predictors of short-term improvement of ischemic stroke. (1st July 2013) - Muscari, Antonio; Puddu, Giovanni M; Serafini, Claudia; Fabbri, Elisa; Vizioli, Luca; Zoli, Marco
<x xml:space="preserve">Abstract</x> Objectives: Several studies have sought factors predictive of early neurological deterioration during acute stroke; however, no study carried out a systematic search for factors capable of predicting early improvement. This investigation is aimed at identifying the variables associated with short-term neurological improvement in patients with ischemic stroke not undergoing thrombolysis. Methods: Two-hundred and fifty-two patients with ischemic stroke were retrospectively examined (mean age: 76·7±10·6 years, 120 males, median delay of admission 8 hours). Stroke severity was assessed both on admission and at discharge (median stay: 4 days) by the National Institutes of Health Stroke Scale (NIHSS). Improvement was defined as a difference between initial and final assessment (∆NIHSS) ≧the median value (2 points). Thus, 127 patients improved (mean change: +3·8 points) and 125 did not (mean change: −1·4 points). Results: During the first 48 hours of hospitalization, 263 clinical, laboratory, instrumental, and therapeutic variables were collected. These were preliminarily compared between two subgroups of patients, improved and non-improved, which were matched for initial NIHSS score, and 17 possible predictors of improvement were found. The subsequent multivariable analysis led to the identification of four factors independently associated with improvement (odds ratio, 95% confidence interval): total anterior circulation syndrome (TACS) (0·20, 0·10-0·39, P<0·0001), aphasia (3·58, 1·89-6·77, P = 0·0001), average systolic blood pressure (0·98 per mmHg, 0·96-0·99, P = 0·002), and age (0·97 per year, 0·94-0·99, P = 0·02). Conclusions: The ischemic strokes that are not TACS, with aphasia, with normal/low blood pressure, or occurring in younger subjects, may have a significant tendency to short-term improvement.